2009
DOI: 10.1089/thy.2008.0421
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of Papillary Thyroid Carcinoma in Recent Years in Greece: The Majority Are Incidental

Abstract: We hypothesize that the prevalence of FTC during the last decade in our center in Greece was very low due to correction of iodine deficiency and a relative increase in the prevalence of microPTC. More than 50% of PTC diagnosed during the last decade were microPTCs that were detected incidentally in older persons with preexisting MNG or a prominent hot nodule. This is one of the highest, if not the highest percentage of microPTCs that were incidentally detected. Despite many of these having features of invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 46 publications
5
26
0
Order By: Relevance
“…It usually presents as a solitary or dominant nodule, but multifocality is not uncommon (3). The incidence of PTC (currently 7.7 per 100,000 person-years in the United States) is higher in women and is rising, predominantly due to the increased detection of occult papillary carcinomas, which have negligible impact on overall mortality (4,5). Total thyroidectomy, which may be followed by ablation with radioactive iodine, is the recommended management for PTC and the prognosis is usually favorable (6).…”
Section: Sumáriomentioning
confidence: 99%
“…It usually presents as a solitary or dominant nodule, but multifocality is not uncommon (3). The incidence of PTC (currently 7.7 per 100,000 person-years in the United States) is higher in women and is rising, predominantly due to the increased detection of occult papillary carcinomas, which have negligible impact on overall mortality (4,5). Total thyroidectomy, which may be followed by ablation with radioactive iodine, is the recommended management for PTC and the prognosis is usually favorable (6).…”
Section: Sumáriomentioning
confidence: 99%
“…Studies have shown a true rise in the incidence of micro and larger forms of papillary thyroid carcinoma in northwestern Spain, a higher incidence of thyroid cancer in the volcanic area of Sicily as well as an increasing prevalence of papillary thyroid carcinoma in Greece [13,14,15,16]. A recent epidemiological study by Farazi [17] showed that in Cypriot women in 2008 thyroid cancer was the second most common cancer after breast cancer, and that the rates for thyroid cancer in women have doubled in just 1 decade.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] For instance, the percentage of FTCs among welldifferentiated carcinomas decreased from 28.1% in the period 1983-1992 to 6.5% in the period 1993-2007 in a very large series from Greece. 5 In Japan, Kakudo et al 6 recently reported that FTCs represented 9.7% among well-differentiated and moderately differentiated carcinomas. In a multiinstitutional study, we are performing in Porto, FTCs composed of 'normal' follicular cells or oncocytic cells represent B5% of clinically evident well-differentiated carcinomas (Magalhães et al, unpublished results).…”
mentioning
confidence: 99%